What causes conspecific plant aggregation? Disentangling the role of dispersal, habitat heterogeneity and plant-plant interactions - Escribano ávila, G. (2016)
© 2015 Nordic Society Oikos. Spatial patterns of plant species are determined by an array of ecologica factors including biotic and abiotic environmental constraints and intrinsic species traits. Thus, an observed aggregated pattern may be the result of short-distance dispersal, the presence of habitat heterogeneity, plant-plant interactions or a combination of the above. Here, we studied the spatial pattern of Mediterranean alpine plant Silene ciliata (Caryophyllaceae) in five populations and assessed the contribution of dispersal, habitat heterogeneity and conspecific plant interactions to observed patterns. For this purpose, we used spatial point pattern analysis combined with specific a priori hypotheses linked to spatial pattern creation. The spatial pattern of S. ciliata recruits was not homogeneous and showed small-scale aggregation. This is consistent with the species' short-distance seed dispersal and the heterogeneous distribution of suitable sites for germination and establishment. Furthermore, the spatial pattern of recruits was independent of the spatial pattern of adults. This suggests a low relevance of adult-recruits interactions in the spatial pattern creation. The difference in aggregation between recruits and adults suggests that once established, recruits are subjected to self-thinning. However, seedling mortality did not erase the spatial pattern generated by seed dispersal, as S. ciliata adults were still aggregated. Thus, the spatial aggregation of adults is probably due to seed dispersal limitation and the heterogeneous distribution of suitable sites at seedling establishment rather than the presence of positive plant-plant interactions at the adult stage. In fact, a negative density-dependent effect of the conspecific neighbourhood was found on adult reproductive performance. Overall, results provide empirical evidence of the lack of a simple and direct relationship between the spatial structure of plant populations and the sign of plant-plant interactions and outline the importance of considering dispersal and habitat heterogeneity when performing spatial analysis assessments.